Texts of the passion : Latin devotional literature and medieval society - Bestul, Thomas H. (Thomas Howard), 1942- (University of Pennsylvania Press, 1996)
In Texts of the Passion, Thomas H. Bestul constructs the literary history of the Latin Passion narratives, placing them within their social, cultural, and historical contexts. He examines the ways in which the Passion is narrated and renarrated in devotional treatises, paying particular attention to the modifications and enlargements of the narrative of the Passion as it is presented in the canonical gospels. Of particular interest to Bestul are the representations of Jews, women, and the body of the crucified Christ. Bestul argues that the greatly enlarged role of the Jews in the Passion narratives of the twelfth and thirteenth centuries is connected to the rising anti-Judaism of the period.
Keywords: Jesus Christ -- Passion -- History of doctrines -- Middle Ages, 600-1500.; Jésus-Christ -- Passion -- Histoire des doctrines -- 600-1500 (Moyen-Âge); Jésus-Christ -- Passion -- Histoire des doctrines -- 600-1500 (Moyen Âge); Jesus Christ; Jésus Christ -- Histoire des doctrines -- 600-1500 (Moyen âge); Jésus Christ -- Passion, dans la littérature.; Christian literature, Latin (Medieval and modern) -- History and criticism.; Devotional literature, Latin (Medieval and modern) -- History and criticism.; Literature and society -- Europe -- History.; Civilization, Medieval, in literature.; Littérature chrétienne latine médiévale et moderne -- Histoire et critique.; Littérature de dévotion latine médiévale et moderne -- Histoire et critique.; Littérature et société -- Europe -- Histoire.; Civilisation médiévale dans la littérature.; RELIGION -- Christian Theology -- Christology.; LITERARY CRITICISM -- Medieval.; Christian literature, Latin (Medieval and modern); Civilization, Medieval, in literature; Devotional literature, Latin (Medieval and modern); Literature and society; Europe; Lijdensgeschiedenis.; Kerk en maatschappij.; Littérature chrétienne latine médiévale et moderne.; Littérature de dévotion latine -- histoire et critique.; 600-1500; Criticism, interpretation, etc.; History